Management and outcomes of lower risk patients presenting with acute coronary syndromes in a multinational observational registry. Issue 11 (10th March 2005) - Devlin, G; Anderson, F A; Heald, S; López-Sendón, J; Avezum, Á; Elliott, J; Dabbous, O H; Brieger, D
Abstract : Objective: To document patterns of risk stratification, management practices, and outcomes among patients with acute coronary syndromes (ACS) presenting without high risk features. Patients: The study was based on 11 885 consecutive patients presenting with non-ST segment elevation ACS enrolled in GRACE (global registry of acute coronary events). Patients without dynamic ST segment changes, positive troponin (or other cardiac markers), or haemodynamic or arrhythmic instability were defined as being at lower risk. Main outcome measures: Management and outcomes were compared with high risk presentations. Results: Of 11 885 patients presenting with unstable angina or non-ST segment elevation myocardial infarction, 4252 (36%) were regarded as being at lower risk. Functional testing for risk stratification was performed in 1163 of 4207 (28%) lower risk and 1531 of 7521 (20%) high risk patients (p < 0.0001). Coronary angiography was performed in 1930 of 4190 (46%) and 3860 of 7544 (51%), and echocardiography in 1692 of 4190 (40%) and 4348 of 7533 (58%) of lower risk and high risk patients, respectively (p < 0.0001 for both). Over one third of patients did not undergo further risk assessment with angiography or functional testing (2746 of 7437 (37%) high risk, 1499 of 4148 (36%) lower risk, not significant). Death occurring in hospital was more likely in the high risk cohort (41 of 4227 (1.0%) lower risk v 215 of 7586 (2.8%) high risk, p < 0.0001), whereas rates of recurrent angina during admission and readmission were similar in both groups (1354 of 4231 (32%) high risk, 2313 of 7587 (31%) lower risk, not significant). In the six months after discharge, death or myocardial infarction occurred in 79 of 3223 (2.5%) lower risk patients and 302 of 5451 (5.5%) high risk patients (p < 0.0001). Conclusions: Globally, further risk stratification after ACS presentation is suboptimal, regardless of presenting characteristics. Although in-hospital death and myocardial infarction are uncommon, recurrent ischaemia is encountered often in both groups. It remains to be seen whether better outcomes may be achieved with wider application of risk stratification and appropriately directed management strategies.